2017
DOI: 10.1108/cb-10-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Highly cited articles in malaria research: a bibliometric analysis

Abstract: Purpose The purpose of this paper is to reveal the bibliometric characteristics of highly cited articles in Malaria research for the period of 1991-2015. Design/methodology/approach The data of highly cited articles for the period of 1991 to 2015 were extracted from the Science Citation Index Expended of Web of Science. The keyword “Malaria” was used as topic term to search documents that contained this word in the title or keyword or abstract of the documents that published in 1991 to 2015. A total of 1,614… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Manuscripts are often published in high-quality journals reflecting the importance of these works in the scientific and clinical communities (Wrafter et al , 2016). Our result is in line with the findings of other studies (Bakri et al , 2017; Bornmann and Leydesdorff, 2015; Gupta and Bala, 2011; Kolle et al , 2017; Iqbal et al , 2019; Martin-Del-Rio et al , 2018; Powell et al , 2016; Tarazona et al , 2018; Wrafter et al , 2016; Zhou et al , 2017). This could be because the authorship of journals with high impact factors are often researchers or the editors of these journals accept articles with a high potential of receiving citations.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Manuscripts are often published in high-quality journals reflecting the importance of these works in the scientific and clinical communities (Wrafter et al , 2016). Our result is in line with the findings of other studies (Bakri et al , 2017; Bornmann and Leydesdorff, 2015; Gupta and Bala, 2011; Kolle et al , 2017; Iqbal et al , 2019; Martin-Del-Rio et al , 2018; Powell et al , 2016; Tarazona et al , 2018; Wrafter et al , 2016; Zhou et al , 2017). This could be because the authorship of journals with high impact factors are often researchers or the editors of these journals accept articles with a high potential of receiving citations.…”
Section: Discussionsupporting
confidence: 94%
“…The USA has published most of the influential articles; this is the finding which is consistent with that of previous studies. Many studies have reported that the USA is the leading country in science production in the domain of medicine and health (Adnan and Ullah, 2018; Bakri et al , 2017; Ellul et al , 2017; Garg et al , 2009; Gu et al , 2015; Kolle et al , 2017; Kolkailah et al , 2019; Martin-Del-Rio et al , 2018; Ozbilgin et al , 2017; Ranson and Lissenden, 2016; Saquib et al , 2017; Tarazona et al , 2018; Van Eijk et al , 2012; Wrafter et al , 2016;). Research activity is dependent on the number of scholars and academics, as well as on the volume of funding available for research (Sweileh et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientometrics therefore gives an aerial view of scientific activity. It basically is a part of library and information science, but it has been judiciously used in numerous other research areas like management [3,4], energy & fuels [5,6], psychology [7,8], Dielectric and bioimpedance research [9], Selfish memes [10], and so on. Bibliometric study is not only celebrated in the field of computer science but is also finding increasing attention in domains such as decision support systems [11,12], bioinformatics [13,14], heuristics [15], big data [16][17][18], and software engineering [19].…”
Section: Introductionmentioning
confidence: 99%